KAJIAN MODEL GINZBURG-LANDAU PADA SUPERKONDUKTOR MESOSKOPIK DAN POTENSI APLIKASINYA PADA SQUID - WISODO, HARI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The role of vortex and anti vortex on the application of a type-II superconductors, JJ-SNS (Josephson Junction-Superconductor Normal Superconductor)and SQUID (Superconducting Quantum Interference Device) has been successfully described using the Ginzburg-Landau models. Furthermore, the study of vortex and antivortex role on the dissipation energy mechanism in the type-II superconductor is based on the TDGL equations. The vortex role in producing the JJ-SNS characteristics and the SQUID mechanism, that can not be explained by a RSJ (Resistively Shunted Junction) model, can be explained using the modified TDGL equations. This study is based on the numerical solution of such equations. The method used is the finite difference method with the FTCS (Forward Time Centere Space) scheme. As a result, the external current density −!Je in the type-II superconductor generates a magnetic pressure difference between the two sides of the material in its path. Such magnetic pressure differences push vortex and anti vortex to move from a high magnetic pressure areas to the lower magnetic pressure areas. An electric field generated by the movement of vortex and anti vortex causes −!Je to release energy as −!Ev · −!Je that it will be converted into a resistive potential differences V. This potential difference fluctuates periodically. The vortices in the energy dissipation mechanism is the fundamental role for producing JJ-SNS characteristics and the mechanism of material with SQUID structure. Result of the study shows that the conditions for a JJ-SNS to work properly whether is the junction width is less than twice of the vortex diameter. This requirement is needed to ensure the vortices can be present in the junction when −!Je flowing on the JJ-SNS. The proximity effects in the junction such as the requirement has been proven. Conversely, the presence of the Josephson effect have not been able verified. The vortex existence will generate the characteristic curve of hVi-Je for the JJ-SNS. The condition is also valid for the material with SQUID structure so that it can be used to measure the −!H . To work properly, Je must be greater or equal to JS c , the material critical current density. The two condition is needed to ensure the existence of vortex evolution in the junctions of material with SQUID structure. The potential difference V at both ends of the material is a basis of the measurements of external magnetic field −!H .